Tourist considerations in hosting a mega sport event: 2010 FIFA World Cup - Bresler , Nerine Cecilia (Applied Studies in Agribusiness and Commerce, 2011)
Tourism enterprises can create public viewing areas where shared enjoyment and heightened emotive experiences could arise, as well as sentiments of patriotism, and ownership of the event itself. But, they must keep their base business happy; to ensure long term loyalty of existing customers.